The Role of Training in Overcoming Leadership and Administrative Challenges - Dhamiri, Abdulrahman M. A. (Archives of Business Research, 2022)
This study aimed to outline the terms education, management and administration to discuss the function of school leaders in overcoming the management and administrative challenges and to find out the limitations amongst them. It is hypothesized that school teachers and head teachers serve to create correct leaders and a correct coaching environment, expand their capabilities of managing staff and conquer administrative challenges. The study was conducted following the descriptive analytical approach where a questionnaire was used for data collection. The questionnaire was distributed among (100) teachers and head teachers at primary, intermediate and secondary schools in Jazan, Saudi Arabia. The study revealed that there is a lack of head teachers’ training at all levels. Training provides the manager with some materials and methods for discovering problems and solving them. It also showed that some head teachers are not flexible enough in dealing with their teaching staff, the students and their parents who follow their children in school from time to time, and this is observed in most schools. The study has some recommendations that the training boards in the Ministry of Education should provide during-service training for teachers at all educational levels – primary, intermediate and secondary schools in Saudi Arabia for all teachers and head teachers – and there should be intensive courses for training teachers and head teachers in terms of during-service training. This will enable them develop their ways and methods of teaching and their abilities to teach and master their classes. Also, teachers and head teachers should benefit from each other by sharing their experiences.